Analysis of the Effects of SAA1 Gene Polymorphisms on Renal Involvement in a Familial Mediterranean Fever Jordanian Population - Ahmed Sheyyab; Rania Wahdan; Al-Ameen Al-Aitan; Mahmoud Abukhadra; Laith Hussein Ayed Naimat (Eurasian Journal of Medicine)
Background: Familial Mediterranean Fever (FMF) is an inherited autosomal recessive disorder resulting from the inheritance of MEFV gene mutations. Patients with FMF are at increased risk of secondary amyloidosis, namely type AA. In some Mediterranean populations, the α genotype was associated with the development of renal amyloidosis, a finding not reproduced in other populations. Our study aimed to assess the association of SAA1 genotypes with renal involvement.